Valorização imobiliária do entorno do Estádio “Verdão” em face da Copa do Mundo de 2014 - Siqueira, Frankes Márcio Batista (2012)
The aim of the present work is to analyze both the strategies and the actions of the social agents that transform the urban space, in particular the State and real estate corporations that influence and/or determine the valorization of the surrounding area of the Verdão Stadium, which was renamed as Arena Pantanal, in the city of Cuiabá. It was evaluated the impact of this phenomenon on the social appropriation of space. It was supposed that many aspects of the real state market valorization influence the use and the appropriation of space, that are considered as aspects of the city's daily life. The recent real estate reestructuring in Cuiabá has produced a new type of space as a result of the preparation for the 2014 World Cup. A great amout of public and private capital has been invested in megaprojects. This study investigates the experience of living in a city during the time of property production and appreciation. The theme seeks to analise and understand the process of the area appropriation and its consequences. The study also presents the cathegories of analysis of the space production and appreciation. The actions and strategies expressed by the plans and projects, the tax values, the price of properties, the laws concerning land appropriation and the publicity concerning the real state enterprises are all important to comprehend the valuation process of the above mentioned area. The result of this process of valorization and speculation carried on by the real state market is a marked housing and social segregation that conflicts with the ideas of social justice and "right to the city" as being conditions to democratize the urban ambient.